Seeing fictions in film : the epistemology of movies - Wilson, George M. (Oxford ; New York : Oxford University Press, 2011)
- Narrative and narration : some rudiments##- Le grand imagier steps out : on the primitive basis of film narration##- The imagined seeing thesis##- Le grand imagier in review##- Elusive narrators in literature##- Elusive narrators in film##- Transparency and twist in narrative fiction film##- Transfiguration and self-conscious narration : on Von Sternberg's last films with Dietrich##- Love and bullshit in Santa Rosa : pastiche in The man who wasn't there.
Includes bibliographical references (p. [215]-218) and index.
boek
Keywords: Motion pictures -- Philosophy; Motion pictures -- Aesthetics; Motion picture audiences; Narration (Rhetoric)